THE EFFECTIVENESS OF GENERATING INTERACTION BETWEEN SCHEMATA AND TEXT (GIST) STRATEGY IN READING COMPREHENSION FOR THE EIGHT GRADERS - Sadrul Fahmi (The Scientia Journal of Social and Legal Studies, 2022)
English as a language is often considered as the international language of the world. There are four skills in English which should be mastered, they are listening, speaking, reading, and writing. The methodology used in this study was experimental, which aims at finding out the influence of particular treatment. the present researcher found some kinds of data, those are students’ mean score and standard deviation, data normality, and data homogeneity. Based on the obtained data, the present researcher found the mean score of the eighth graders of MTs NW Pagutan in the school year 2014-2015. In pre-test the mean score was 58 and the standard deviasion was 10.66, the mean score of students in post test was 79 and the standard deviasion was 12.65. The hypothesis of this study is GIST strategy was effective in teaching reading comprehension of the eighth graders at MTs NW Pagutan in the school year 2014-2015’’. Based on the obtained data in the previous chapter, the present researcher comes to a set of conclusion: The students’ mean score of experimental group in post-test was higher than in pre test. It means that the students in post test were better than those in pre test, and Generating Interaction between Schemata and Text strategy is effective in reading comprehension for the eighth graders at MTs NW Pagutan in the school year 2014-2015 was effective because the result of hypothesis testing showed that the t-test was higher than t-table.